Extracellular regulated kinase 1/2 signaling is a critical regulator of interleukin-1β-mediated astrocyte tissue inhibitor of metalloproteinase-1 expression. - Jerel Fields; Irma E Cisneros; Kathleen Borgmann; Anuja Ghorpade (PLoS ONE)
Astrocytes are essential for proper central nervous system (CNS) function and are intricately involved in neuroinflammation. Despite evidence that immune-activated astrocytes contribute to many CNS pathologies, little is known about the inflammatory pathways controlling gene expression. Our laboratory identified altered levels of tissue inhibitor of metalloproteinase (TIMP)-1 in brain lysates from human immunodeficiency virus (HIV)-1 infected patients, compared to age-matched controls, and interleukin (IL)-1β as a key regulator of astrocyte TIMP-1. Additionally, CCAAT enhancer binding protein (C/EBP)β levels are elevated in brain specimens from HIV-1 patients and the transcription factor contributes to astrocyte TIMP-1 expression. In this report we sought to identify key signaling pathways necessary for IL-1β-mediated astrocyte TIMP-1 expression and their interaction with C/EBPβ. Primary human astrocytes were cultured and treated with mitogen activated protein kinase-selective small molecule inhibitors, and IL-1β. TIMP-1 and C/EBPβ mRNA and protein expression were evaluated at 12 and 24 h post-treatment, respectively. TIMP-1 promoter-driven luciferase plasmids were used to evaluate TIMP-1 promoter activity in inhibitor-treated astrocytes. These data show that extracellular regulated kinase (ERK) 1/2-selective inhibitors block IL-1β-induced astrocyte TIMP-1 expression, but did not decrease C/EBPβ expression in parallel. The p38 kinase (p38K) inhibitors partially blocked both IL-1β-induced astrocyte TIMP-1 expression and C/EBPβ expression. The ERK1/2-selective inhibitor abrogated IL-1β-mediated increases in TIMP-1 promoter activity. Our data demonstrate that ERK1/2 activation is critical for IL-1β-mediated astrocyte TIMP-1 expression. ERK1/2-selective inhibition may elicit a compensatory response in the form of enhanced IL-1β-mediated astrocyte C/EBPβ expression, or, alternatively, ERK1/2 signaling may function to moderate IL-1β-mediated astrocyte C/EBPβ expression. Furthermore, p38K activation contributes to IL-1β-induced astrocyte TIMP-1 and C/EBPβ expression. These data suggest that ERK1/2 signals downstream of C/EBPβ to facilitate IL-1β-induced astrocyte TIMP-1 expression. Astrocyte ERK1/2 and p38K signaling may serve as therapeutic targets for manipulating CNS TIMP-1 and C/EBPβ levels, respectively.